PHYSICS LEARNING MEDIA IN THE FORM OF SONGS AND MUSIC VIDEOS ON THE TOPIC OF TEMPERATURE AND HEAT: MEDIA PEMBELAJARAN FISIKA BERUPA LAGU DAN VIDEO KLIP PADA MATERI SUHU DAN KALOR - Aziz Setiawan; Hadi Nasbey; Upik Rahma Fitri (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
This research aims to produce interactive learning media using video clips and songs in physics lessons on the topic of temperature and heat. The research method employed is Research and Development (R&D) with the 4D model (Define, Design, Develop, and Disseminate). The steps in this development include needs analysis, product design, product validation by experts, product testing with students and educators, and evaluation. Based on the needs analysis conducted by the researcher in five high schools in Jabodetabek through a questionnaire responded to by 38 eleventh-grade students, 76.3% of students found physics lessons difficult to understand, and 78.9% of students found physics learning thus far to be boring. 100% of students enjoy listening to music/songs. 94.7% of students are interested in using songs and video clips as physics learning media, and 94.7% of students agree to develop physics learning media on the topic of temperature and heat in the form of songs and video clips.